A case series of rare pathologies of the aorta and the aortic arch in adolescents and younger adults: Transfer of experience for an individualized approach - Carrel, Thierry; Sharipov, Islamjan; Jalilov, Adham; Sromicki, Juri; Vogt, Paul Robert (Frontiers in Cardiovascular Medicine, 2022)
Objective While aneurysm of the aortic root, interrupted aortic arch, and aortic coarctation are the most frequent aortic diseases in adolescents and younger adults, there are a number of rare pathologies of the thoracic aorta that need individualized treatment. Patients We present a small case series of unusual aortic pathologies in patients presenting with a broad spectrum of symptoms: tiredness, dysphagia, dyspnea, arterial hypertension, renal failure, and claudication. (1). Segmental agenesia of the descending aorta. (2). Balanced double aortic arch with complete vascular ring. (3). Right descending aortic arch, left lusorian artery with Kommerell diverticulum. (4). Large patent ductus (2.5 cm) and ventricular septal defect. (5). Aneurysm of the aortic arch in the presence of tuberous sclerosis. (6). Pseudo-aneurysm of the proximal descending aorta following coarctation patch plasty. (7). Supravalvular aortic stenosis combined with severe aortic valve stenosis. (8). Pseudo-aneurysm following ascendens-to-descendens bypass because of recurrent coarctation. (9). Takayasu arteriitis with severe stenosis in the thoraco-abdominal aorta. Results The following procedures were performed, using individualized cardiopulmonary bypass, canulation and cerebral protection strategies. (1). Ascending to supraceliac extra-anatomic bypass. (2). Division of the ductus ligament and of the anterior aortic arch distally to the left subclavian artery. (3). Excision of the Kommerell diverticulum and translocation of the left subclavian artery. (4). Patch closure of the aorto-pulmonary window (patent ductus) and closure of the ventricular septal defect. (5). Complete aortic arch replacement combined with debranching of the supra-aortic vessels. (6). Graft interposition of the proximal descending aorta. (7). Enlargement of the ascending aorta and aortic valve replacement. (8). Exclusion of the pseudo-aneurysm, end-to-side graft interposition. (9). Ascending aorta to infrarenal aorta or ascending to bi-iliac artery bypass (planned). All patients were operated on without operative mortality. One patient died in-hospital from pulmonary complications one week after surgery. One patient is still awaiting surgery. All other patients recovered very well from the operation and did not show any residual symptoms. Conclusion Rare pathologies of the thoracic aorta in younger patients may cause a broad spectrum of unusual symptoms; in some of them, diagnosis is delayed. Cross-sectional imaging is mandatory for optimal operative planning Surgical treatment can be performed with very satisfying results. The prognosis of these patients is usually favorable following surgery.